Patient-maintained versus anaesthetist-controlled propofol sedation during elective primary lower-limb arthroplasty performed under spinal anaesthesia: a randomised controlled trial. (January 2022) - Hewson, David W.; Worcester, Frank; Sprinks, James; Smith, Murray D.; Buchanan, Heather; Breedon, Philip; Hardman, Jonathan G.; Bedforth, Nigel M.
Abstract: Background: Patient-maintained propofol TCI sedation (PMPS) allows patients to titrate their own target-controlled infusion (TCI) delivery of propofol sedation using a handheld button. The aim of this RCT was to compare PMPS with anaesthetist-controlled propofol TCI sedation (ACPS) in patients undergoing elective primary lower-limb arthroplasty surgery under spinal anaesthesia. Methods: In this single-centre open-label investigator-led study, adult patients were randomly assigned to either PMPS or ACPS during their surgery. Both sedation regimes used Schnider effect-site TCI modelling. The primary outcome measure was infusion rate adjusted for weight (expressed as mg kg −1 h −1 ). Secondary outcomes measures included depth of sedation, occurrence of sedation-related adverse events and time to medical readiness for discharge from the postanaesthsia care unit (PACU). Results: Eighty patients (48 female) were randomised. Subjects using PMPS used 39.3% less propofol during the sedation period compared with subjects in group ACPS (1.56 [0.57] vs 2.57 [1.33] mg kg −1 h −1 ; P <0.001), experienced fewer discrete episodes of deep sedation (0 vs 6; P =0.0256), fewer airway/breathing adverse events (odds ratio [95% confidence interval]: 2.94 [1.31–6.64]; P =0.009) and were ready for discharge from PACU more quickly (8.94 [5.5] vs 13.51 [7.2] min; P =0.0027). Conclusions: Patient-maintained propofol sedation during lower-limb arthroplasty under spinal anaesthesia results in reduced drug exposure and fewer episodes of sedation-related adverse events compared with anaesthetist-controlled propofol TCI sedation. To facilitate further investigation of this procedural sedation technique, PMPS-capable TCI infusion devices should be submitted for regulatory approval for clinical use. Clinical trial registration: ISRCTN29129799.